Understanding Failure and Runout Mechanisms of the Flims Rockslide/Rock Avalanche - Aaron, Jordan; Wolter, Andrea; Loew, Simon; Volken, Stefan (Frontiers in Earth Science, 2020)
The Flims rockslide/rock avalanche is the largest long runout landslide in Europe. This event provides a unique opportunity to study the pre-failure and failure behavior of a large rock slope, as both the source zone and deposit of this event are accessible. In this study, we perform engineering geological and geomorphic field mapping as well as stability and runout modelling in order to explore the preconditioning and triggering factors that resulted in failure of this event, and to infer the mechanisms that governed its runout. By combining these analyses, we qualitatively comment on the mechanisms that lead to the transition from a rockslide to a long runout, catastrophic rock avalanche. Our engineering geological and geomorphic field mapping has revealed that the Flims rockslide/rock avalanche failed along a sliding zone that features numerous, large scale steps. Previous work at the site, as well as new analysis of thin sections, has revealed the presence of marl-like layers within the failed stratigraphic unit. Our stability analysis shows that the presence of low strength layers at the depth of the rupture surface is required for failure to initiate, and that failure could be triggered either by strong seismic shaking, elevated pore-water pressures, or a combination of both. The results of the runout analysis show that this event likely remained coherent for a large portion of its motion, and that liquefaction of alluvial sediments at the toe of the slope may have enhanced the runout distance of this rock avalanche. Combining the mapping, stability and runout modelling has shown that the basal shear strength required for the runout analysis is approximately 6° to 10° lower than that back-analysed for the stability of this event. Thus, a mechanism to reduce strength along the rupture surface immediately following the initial instability was required for catastrophic failure of this event. This mechanism is poorly understood at present, but is likely crucial for understanding the transition from an initially stable slope to a catastrophic, long runout rock avalanche.